Purchase Decision Factors: Men's Biore Cleanser for Business Students: Faktor-faktor yang Mempengaruhi Keputusan Pembelian: Pembersih Wajah Men's Biore bagi Mahasiswa Bisnis - Raden Dicky Anugrah Pamungkas; Lilik Indayani (Academia Open, 2023)
This quantitative research study aims to investigate the factors influencing the purchase decisions of Men's Biore Facial Cleanser among students from the Faculty of Business, Law, and Social Sciences in Sidoarjo. Through the use of a questionnaire-based survey distributed to 100 consumers, the study employed multiple linear regression analysis to examine the influence of product quality, price, and brand image on purchasing decisions. The results revealed that product quality, price, and brand image individually had a significant impact on the purchase decisions. Moreover, when considered together, these factors collectively played a significant role in influencing the purchasing decisions of the students. These findings provide valuable insights for marketers and can guide their strategies to effectively target and engage with the student population in relation to Men's Biore Facial Cleanser. Highlights: The study explores the factors influencing purchase decisions among business students. Product quality, price, and brand image significantly impact the purchasing decisions. Insights from this research can guide marketers in targeting and engaging with business students. Keywords: Purchase decisions, Product quality, Price, Brand image, Business students